The effect of governance quality on economic growth: Based on China's provincial panel data - Jiandang Liu; Jie Tang; Bo Zhou; Zhijun Liang (Economies, 2018)
This paper investigates the impact of governance quality on economic growth in China. After developing a theoretical framework for the effect of governance quality on local economic growth, this article studies the panel data in provincial regions over the period 2001-2015 by constructing a new comprehensive index of provincial governance, and checks the robustness of the empirical findings from four aspects. The results show that governance quality has a positive effect on economic growth, due to good governance strengthening the 'helping hand' or weakening the 'grabbing hand' of power. Governance quality presents diminishing marginal returns, which means that the high-speed economic growth effect becomes less and less, while the high-quality economic development effect becomes more and more. Higher governance quality could bring a high-speed economic growth effect in the western region, while higher governance quality could bring a high-quality economic development effect in the eastern region. Compared with fixed-asset investment, human capital has played a more important role in economic growth. In order to promote the sustainable development of China's economy, policy makers should improve local governance quality, strengthen the capacity of independent innovation, and promote the accumulation of high-quality human capital.
Keywords: C51; O43; P25; 330; good governance; provincial governance; diminishing marginal returns; high-speed economic growth effect; high-quality economic development effect; endogeneity; region difference; robustness check